PROGRAM OF AES ORBIT DETERMINATION FROM MEASUREMENT DATA OF ASTRONOMICAL STATION (“ORBITA – M”) - Sheptun, A. D.; Kolesnik, S. Ya.; Paltsev, N. G. (Одеські астрономічні публікації, 2017)
A program is developed of determining AES orbits from measurement data of one or several astronomical stations. Its algorithm is rather stable to small errors of measurements and permits to use data with low accuracy for calculations. The use of several transits data enables to increase precision of orbital semi-major axe determination by nearly 10000 times.